1999
DOI: 10.1046/j.1365-4362.1999.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in Yemen

Abstract: Cutaneous leishmaniasis in this region seems to be endemic, has a long chronic course, shows a highly positive smear even 1-6 years after onset, and gives an inadequate response to prolonged systemic therapy. Further epidemiologic studies and taxonomic differentiation of the species are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…This age-based incidence of CL is similar to previous studies on this subject in both Syria and Turkey. 7,9,[11][12][13][14][15] Interestingly, in contrast to Syrian patients, a higher female (58.5%) to male (41.5%) ratio was observed in Turkish patients. Similar reports of higher female incidence were observed in a recent study in Nizip, southern Turkey (61% female, 39% male), which is geographically close to Sanliurfa and is also endemic for CL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This age-based incidence of CL is similar to previous studies on this subject in both Syria and Turkey. 7,9,[11][12][13][14][15] Interestingly, in contrast to Syrian patients, a higher female (58.5%) to male (41.5%) ratio was observed in Turkish patients. Similar reports of higher female incidence were observed in a recent study in Nizip, southern Turkey (61% female, 39% male), which is geographically close to Sanliurfa and is also endemic for CL.…”
Section: Discussionmentioning
confidence: 89%
“…Previous reports have shown that CL lesions are generally seen on uncovered parts of the body and less often on covered areas. 1,14,[20][21][22][23][24] This is not surprising since these are the areas that are readily accessible by the sandfly. A study in Turkey by Gurel and others 9 reported the location of CL lesions as 57.5% in the head and neck region, 32.2% in the upper extremities, 10.2% in the lower extremities, 0.8% in oral mucosa, 0.2% on the trunk, and no mucosal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmaniasis was endemic in Yemen [2]. It has been recognized as a public health problem predominated by infection with the highest burden of Leishmaniasis, but has not been fully documented [18]. CL is endemic and most of the cases are registered in Lahg, Abun, Hagga and Sa’adah Taiz Governorates [3].…”
Section: Resultsmentioning
confidence: 99%
“…Systemic Pentostam is the drug of choice. In view of the cases of dissemination occurring despite Pentostam therapy, the addition of another systemic drug, such as rifampicin, 20,21 can be considered where Pentostam proves to be inadequate. Topical drugs such as clotrimazole may also play a role in therapy 22 …”
Section: Discussionmentioning
confidence: 99%